1979
DOI: 10.1111/j.1432-1033.1979.tb04272.x
|View full text |Cite
|
Sign up to set email alerts
|

ΔpH Induced Calcium Fluxes in Rat Liver Mitochondria

Abstract: The paper reports an investigation on ΔpH‐driven Ca2+ fluxes in rotenone‐treated rat liver mitochondria. The H+ concentration gradient (acidic inside) required to drive Ca2+ influx is obtained from the K+ concentration gradient through a H+/K+ exchange. The rate of H+/K+ exchange is very low in native mitochondria and is markedly enhanced by the electroneutral ionophore nigericin. The rate of Ca2+ influx depends on the rate of generation of ΔpH; it is negligible in native mitochondria and fast after nigericin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…On a protein basis the chloroplastic Ca'+ influx rates are similar to those of plant [31] and rat liver mitochondria [27]. From a comparison of k,,, values it has been concluded that the affinity of the mitochondrial system is at least lo-fold lower than the affinity of the plasma membrane system [23].…”
Section: Rates and Affinitymentioning
confidence: 67%
See 2 more Smart Citations
“…On a protein basis the chloroplastic Ca'+ influx rates are similar to those of plant [31] and rat liver mitochondria [27]. From a comparison of k,,, values it has been concluded that the affinity of the mitochondrial system is at least lo-fold lower than the affinity of the plasma membrane system [23].…”
Section: Rates and Affinitymentioning
confidence: 67%
“…Comparison with mitochondrial Cd" influx systems Ca*+ influx into animal [25,27] and plant mitochondria [23,24] is mediated by an electrogenic uniport-carrier system similar to that described here for chloroplasts. The influx is sensitive to ruthenium red [24-271 and has been shown to be under the control of AE [28,29].…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Pore opening was rnonitored as the apparent absorbance change at 540 nm following membrane permeabilization to solutes. Although similar in principle to the incubation conditions of a previous study [I51 and to those employed by others [21,221, the use of potassium gluconate rather than sucrose ensured that the Donnan potential was collapsed and thus that an inside-acidic ApH did not form, which could in principle sustain a Ca2+ concentration gradient in the presence of FCCP and A23187 [23].…”
Section: Resultsmentioning
confidence: 95%
“…Although a pH gradient can indeed drive Ca 21 accumulation, which is more readily observed in deenergized mitochondria (Bernardi and Azzone, 1979), in energized mitochondria the driving force for Ca 21 accumulation is the electrical potential difference rather than the delta pH.…”
Section: Discussionmentioning
confidence: 99%